A Study on Design and Fabrication of Red Mud Filtration Machine: Improving Efficiency of Red Mud Filtration for Alumina Refineries (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Special relation to red moth (RM) or bauxite residue produced by different aluminium industries in India, as often happens in industrial waste. This is an important topic for protection and the community. For alumina refineries, handling of red or bauxite residues is a key concern. The amount of 2,5 tons of red mud residue must be manufactured for each tonne of Al2O3 processed at the alumina refinery. The quantity of residue varies depending on the quality of the bauxite and the site of the alumina refinery. Most of the red mud has been deposited in mud-lakes andor impoundment areas in recent years this has been standard procedure at worldwide alumina refineries. Many refineries choose to manufacture a red-solid cake, friable and transportable by truck and conveyor, for pressure filtration. For industrial purposes, the bulky Red Mud behaviour and low caustic content are important problems for custom superior filtration technologies. The first part of the study text deals with a Red Mud Filtration and dieting process for the production of mud cake in general for industrial use and the efficient utilization of the filtering phase. The design and filtration of the system together with various components is done with CAD and CAM software (CATIA). The following section focuses on experimental procedures to increase the performance of the filtration system by calculating the design. As a consequence, the sodium content of red mud slurry decreased fairly from 10 to 20. This makes the creation of red mud cake smoother compared with other filters well understood. Therefore the efficiency with regard to moisture content of the red mud filter machine is improved.